Metamorphoses - CURNOW, Trevor (Utopía y Praxis Latinoamericana, 2016)
Our lives can be transformed by our experiences in many different ways. Sometimes an experience is so powerful that it makes us see the world in a completely different way. However, seeing the world differently is not necessarily the same as seeing the world better. We may not be able to resist an experience, but that does not mean that we learn the correct lesson from it. It is necessary to distinguish psychological force from epistemological weight.